PENGARUH BANKRUPTCY RISK, SIZE DAN BOOK-TO-MARKET PERUSAHAAN TERHADAP IMBAL HASIL - Utama, Cynthia Afriani; Lumondang, Astari (UI Scholars Hub, 2009)
This study investigates: a) the influence o f firm size and book-to-market ratio on bankruptcy risk, and b) the effect o f bankruptcy risk, firm size, and book-to-market ratio on subsequent return. The study employs Altman Z-Score and Ohlson 0-Score as proxies for bankruptcy risk. The results show that size has positive impact on Bankruptcy Risk measured by Altman Z-Score while book-to-market has positive impact on bankruptcy risk measured Ohlson 0-Score. Furthermore, the results show that none o f the variables has significant impact on subsequent return. Overall, this study asserts Dichev’s (1998) findings that bankruptcy risk is not rewarded by higher stock returns and therefore not systematic.